Hydatidosis in Human Beings in Al-Jabal Al- Akhdar Area in Libya - Al-Khalidi, Nahad Walli (Al-Mukhtar Journal of Sciences, 1998)
Fourteen surgically confirmed cases of hydatidosis in Al-Jabal area in Libya were investigated. The infection rate was 1% (14 cases out of 1399 surgical cases). among the patients attended Al-Thawrah Hospital in El- Beida Libya . Hydatid cysts were found in all ages (5 to 50 years ) of the patients. Eleven hydatid cyst patients were female 5 – 50 Years old and only 3 patients were male of 29 - 50 years old. The cysts in 13 cases were single cyst and were almost spherical in shape and about 4 - 13 cms in diameter. Only one case contained multiple small cysts (6 cysts about 1 to 2 cms in diameter) in the lungs. Hydatid cysts of 6 patients were located in the liver and of 6 of the patients were in the peritoneal cavity, one patient in the spleen and an other in the lungs . The cysts of 12 patients was partially calcified and sterile . It was found that the females were more exposed to infection than males and that the size of the cysts increased with the age of the patients .